Emerging trends in computational biology, bioinformatics, and systems biology : algorithms and software tools - Tran, Quoc-Nam; Arabnia, Hamid (Emerging trends in computer science & applied computing., 2015)
This book discusses the latest developments in all aspects of computational biology, bioinformatics, and systems biology and the application of data-analytics and algorithms, mathematical modeling, and simulation techniques. It addresses the development and application of data-analytical and theoretical methods, mathematical modeling and computational simulation techniques to the study of biological and behavioral systems; presents a systematic approach for storing, retrieving, organizing and analyzing biological data using software tools with applications; provides a systems biology perspective including general guidelines and techniques for obtaining, integrating and analyzing complex data sets from multiple experimental sources using computational tools and software. --